2022
DOI: 10.1111/pde.14978
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous manifestations of obesity in Turkish children: A comparative study

Abstract: Background Cutaneous changes in obese adults have been investigated in numerous studies, but this issue has not been adequately investigated in children. Objectives We aimed to determine the prevalence of skin manifestations in children with obesity by comparing them to normal‐weight children. Methods A cross‐sectional study was conducted between June 2017 and January 2019 in which 82 children with obesity and 86 normal‐weight healthy control children were enrolled. Study participants had detailed full‐body sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 31 publications
5
8
0
2
Order By: Relevance
“…Accordingly, the prevalence of tinea pedis (12%) is markedly elevated in children with obesity compared to schoolchildren in the general population, in whom the prevalence ranges from 2.69% ( 32 ) to 5.7% ( 33 ). While dermatomycosis occurred substantially more frequently in Egyptian children (21.9%), the results of other previous studies are comparable to the general population ( 15 , 16 ). Similarly, in another German study examining minors with diabetes mellitus, tinea pedis was observed only in 1.6% of the participants ( 34 ).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Accordingly, the prevalence of tinea pedis (12%) is markedly elevated in children with obesity compared to schoolchildren in the general population, in whom the prevalence ranges from 2.69% ( 32 ) to 5.7% ( 33 ). While dermatomycosis occurred substantially more frequently in Egyptian children (21.9%), the results of other previous studies are comparable to the general population ( 15 , 16 ). Similarly, in another German study examining minors with diabetes mellitus, tinea pedis was observed only in 1.6% of the participants ( 34 ).…”
Section: Discussionsupporting
confidence: 71%
“…To the best of our knowledge, this is the largest study of the clinical spectrum of cutaneous lesions, their associations with anthropometric data and their impacts on QoL in children and adolescents with obesity. Compared to a recent study including 82 pediatric patients with overweight and obesity, the mean BMI SDS values were similar (2.74 ± 0.72 vs 2.60 ± 0.5) ( 15 ). Furthermore, four studies with a similar dermatological focus and >80 included patients ( n = 82 ( 14 ), n = 100 ( 26 ), n = 510 ( 27 ), n = 91 ( 16 )) did not report the BMI SDS values of the recruited patients.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In addition, 38.9% of subjects showed reduced dermatological quality of life [ 214 ]. Striae distensae are also the most frequently observed dermatologic condition among children with obesity, according to the study by Güven et al [ 215 ].…”
Section: Non-metabolic Complications Of Obesity In Childrenmentioning
confidence: 99%